In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor

Inactive enzymatic mutant proteins (phosphoglycerate mutase and enolase) as sugar binders for ribulose-1,5-bisphosphate regeneration reactors - De, Dinesh; Dutta, D.; Kundu, M.; Mahato, S.; Schiavone, M. T.; Chaudhuri, S.; Giri, Ashok P.; Gupta, Vidya; Bhattacharya, S. K. (Microbial Cell Factories, 2005)
Background: Carbon dioxide fixation bioprocess in reactors necessitates recycling of D- ribulose1,5-bisphosphate (RuBP) for continuous operation. A radically new close loop of RuBP regenerating reactor design has been proposed that will harbor enzyme-complexes instead of purified enzymes. These reactors will need binders enabling selective capture and release of sugar and intermediate metabolites enabling specific conversions during regeneration. In the current manuscript we describe properties of proteins that will act as potential binders in RuBP regeneration reactors. Results: We demonstrate specific binding of 3-phosphoglycerate (3PGA) and 3-phosphoglyceraldehyde ( 3PGAL) from sugar mixtures by inactive mutant of yeast enzymes phosphoglycerate mutase and enolase. The reversibility in binding with respect to pH and EDTA has also been shown. No chemical conversion of incubated sugars or sugar intermediate metabolites were found by the inactive enzymatic proteins. The dissociation constants for sugar metabolites are in the micromolar range, both proteins showed lower dissociation constant (Kd) for 3-phosphoglycerate ( 655 - 796 mu M) compared to 3-phosphoglyceraldehyde ( 822 - 966 mu M) indicating higher affinity for 3PGA. The proteins did not show binding to glucose, sucrose or fructose within the sensitivity limits of detection. Phosphoglycerate mutase showed slightly lower stability on repeated use than enolase mutants. Conclusions: The sugar and their intermediate metabolite binders may have a useful role in RuBP regeneration reactors. The reversibility of binding with respect to changes in physicochemical factors and stability when subjected to repeated changes in these conditions are expected to make the mutant proteins candidates for in-situ removal of sugar intermediate metabolites for forward driving of specific reactions in enzyme-complex reactors.

Identification of Indian pathogenic races of fusarium oxysporum f. sp ciceris with gene specific, ITS and random markers - Gurjar, Gayatri; Barve, Maneesha; Giri, Ashok P.; Gupta, Vidya (Mycologia, 2009)
In this study we demonstrate the synergistic use of gene-specific markers, ITS-RFLP, ISSR and AFLP for distinguishing Indian F. oxysporum f. sp. ciceris races. We also report for the first time that F. oxysporum f. sp. ciceris race 3, a wilt pathogen of chickpea in India, is actually E proliferatum based on phylogenetic analysis with EF-1 alpha sequence data. E oxysporum f. sp. ciceris races 1, 2 and 4 were easily distinguished from ``race 3'' (F. proliferatum) by PCR amplification with oligonucleotides designed from conserved regions of Hop78 transposon (Hop 78), cutinase (Cut), desaturase (Dst). F oxysporum f. sp. ciceris race 4 was distinguished with the xylanase 3 (xyl3) gene by absence of amplification product only in this race. The Xyl3 amplified-DNA fragment isolated and sequenced from E oxysporum f. sp. ciceris race I was similar to the F-xylanase (Xyl3) gene of E oxysporum f. sp. lycopersici. A TELD motif, which is characteristic of the F-xylanases family, was detected within the deduced amino acid sequence of F. oxysporum f. sp. ciceris. Similarly the F oxysporum f. sp. ciceris Hop78 DNA fragment, which identified ``race 3'' (E proliferatum), was homologous to the Hop78 transposon of E oxysporum f. sp. melonis, including the 100 amino acid conserved domain and the characteristic CCHC motif. The internal transcribed spacer region-restriction fragment length polymorphism (ITS-RFLP) approach along with intersimple sequence repeat (ISSR) method also differentiated ``race 3'' (F. proliferatum). Races 1 and 2 were identified by unique AFLP patterns. Sequence characterization of race-specific AFLP products revealed significant homologies of these sequences with metabolically important genes.
Keywords: AFLP; F. oxysporum f. sp ciceris races; gene specific amplification; ISSR; ITS-RFLP; race delineation; sequence characterization; translation elongation factor (EF-1 alpha)

Interaction of recombinant CanPIs with helicoverpa armigera gut proteases reveals their processing patterns, stability and efficiency - Mishra, Manasi; Tamhane, Vaijayanti A.; Khandelwal, Neha; Kulkarni, Mahesh J.; Gupta, Vidya S.; Giri, Ashok P. (Proteomics, 2010)
Six diverse representative Capsicum annuum (common name: hot pepper; Solanaceae) protease inhibitor genes, viz CanPI-5, -7, -13, -15, -19, and 22 comprising 1-4 inhibitory repeat domains (IRDs), were cloned and expressed in Pichia pastoris. The recombinant proteins were evaluated for their interactions with bovine trypsin, chymotrypsin, and Helicoverpa armigera gut proteases (HGP) using electrophoretic (native and denaturing) and mass spectrometric (MALDI-TOF-MS in combination with intensity fading assays) techniques. These techniques allow qualitative and semiquantitative analysis of multiple and processed IRDs of purified recombinant Capsicum annuum proteinase inhibitor (rCanPI) proteins. rCanPIs showed over 90% trypsin inhibition, varying chymotrypsin inhibition depending on the number of respective IRDs and over 60% inhibition of total HGP. rCanPI-15 that has only one IRD showed exceptionally low inhibition of these proteases. Interaction studies of rCanPIs with proteases using intensity fading-MALDI-TOF-MS revealed gradual processing of multi-IRD rCanPIs into single IRD forms by the action of HGP at the linker region, unlike their interactions with trypsin and chymotrypsin. Intensity fading-MALDI-TOF-MS assay showed that CanPI-13 and -15, possessing single IRD and expressed predominantly in stem tissue are degraded by HGP; indicating their function other than defense. In vitro and in vivo studies on rCanPI-5 and -7 showed maximum inhibition of HGP isoforms and their processed IRDs were also found to be stable in the presence of HGP. Even single amino acid variations in IRDs were found to change the HGP specificity like in the case of HGP-8 inhibited only by IRD-12. The presence of active PI in insect gut might be responsible for changed HGP profile. rCanPI-5 and -7 enhanced HGP-7, reduced HGP-4, -5, -10 expression and new protease isoforms were induced. These results signify isoform complexity in plant PIs and insect proteases.
Keywords: CanPI; H. armigera gut proteases; Intensity fading MALDI-TOF-MS; Pin-II; Plant proteomics; Plant-insect interaction

Identification and expression profiling of helicoverpa armigera microRNAs and their possible role in the regulation of digestive protease genes - Lomate, Purushottam R.; Mahajan, Neha S.; Kale, Sandip M.; Gupta, Vidya S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2014)
The present investigation is an effort to determine the possible roles of microRNAs (miRNAs) in the regulation of protease gene expression in Helicoverpa armigera upon exposure to plant protease inhibitors (PIs). Using Illumina platform, deep sequencing of 12 small RNA libraries was performed from H. armigera larvae fed on artificial diet (AD) or recombinant Capsicum annuum PI-7 (rCanPI-7) incorporated diet, at various time intervals (0.5, 2, 6, 12, 24, and 48 h). Sequencing data were analyzed with miRDeep2 software; a total of 186 unique miRNAs were identified from all the 12 libraries, out of which 96 were conserved while 90 were novel. These miRNAs showed all the conserved characteristics of insect miRNAs. Homology analysis revealed that most of the identified miRNAs were insect-specific, and more than 50 miRNAs were Lepidoptera-specific. Several candidate miRNAs (conserved and novel) were differentially expressed in rCanPI-7 fed larvae as compared to the larvae fed on AD. H. armigera miRNAs were found to have target sites in several protease genes as well as in protease regulation related genes such as serine PI and immune reactive PI. As expected, negative correlation in the relative abundance miRNAs and their target mRNAs was evident from qualitative real time polymerase chain reaction analysis. The investigation revealed potential roles of miRNAs in H. armigera protease gene regulation. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Deep sequencing; Helicoverpa armigera; miRNAs; Protease gene regulation; Protease inhibitors

Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs

Insecticidal potential of defense metabolites from ocimum kilimandscharicum against helicoverpa armigera - Singh, Priyanka; Jayaramaiah, Ramesha H.; Sarate, Priya; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J.; Giri, Ashok P. (Plos One, 2014)
Genus Ocimum contains a reservoir of diverse secondary metabolites, which are known for their defense and medicinal value. However, the defense-related metabolites from this genus have not been studied in depth. To gain deeper insight into inducible defense metabolites, we examined the overall biochemical and metabolic changes in Ocimum kilimandscharicum that occurred in response to the feeding of Helicoverpa armigera larvae. Metabolic analysis revealed that the primary and secondary metabolism of local and systemic tissues in O. kilimandscharicum was severely affected following larval infestation. Moreover, levels of specific secondary metabolites like camphor, limonene and beta-caryophyllene (known to be involved in defense) significantly increased in leaves upon insect attack. Choice assays conducted by exposing H. armigera larvae on O. kilimandscharicum and tomato leaves, demonstrated that O. kilimandscharicum significantly deters larval feeding. Further, when larvae were fed on O. kilimandscharicum leaves, average body weight decreased and mortality the larvae increased. Larvae fed on artificial diet supplemented with O. kilimandscharicum leaf extract, camphor, limonene and beta-caryophyllene showed growth retardation, increased mortality rates and pupal deformities. Digestive enzymes of H. armigera - namely, amylase, protease and lipase- showed variable patterns after feeding on O. kilimandscharicum, which implies striving of the larvae to attain required nutrition for growth, development and metamorphosis. Evidently, selected metabolites from O. kilimandscharicum possess significant insecticidal activity.

Improved tolerance against helicoverpa armigera in transgenic tomato over-expressing multi-domain proteinase inhibitor gene from capsicum annuum - Tanpure, Rahul S.; Barbole, Ranjit S.; Dawkar, Vishal V.; Waichal, Yashashree A.; Joshi, Rakesh S.; Giri, Ashok P.; Gupta, Vidya S. (Physiology and Molecular Biology of Plants, 2017)
Plant proteinase inhibitors (PIs) are plant defense proteins and considered as potential candidates for engineering plant resistances against herbivores. Capsicum annuum proteinase inhibitor (CanPI7) is a multi-domain potato type II inhibitor (Pin-II) containing four inhibitory repeat domains (IRD), which target major classes of digestive enzymes in the gut of Helicoverpa armigera larvae. Stable integration and expression of the transgene in T1 transgenic generation, were confirmed by established molecular techniques. Protein extract of transgenic tomato lines showed increased inhibitory activity against H. armigera gut proteinases, supporting those domains of CanPI7 protein to be effective and active. When T1 generation plants were analyzed, they exhibited antibiosis effect against first instar larvae of H. armigera. Further, larvae fed on transgenic tomato leaves showed delayed growth relative to larvae fed on control plants, but did not change mortality rates significantly. Thus, better crop protection can be achieved in transgenic tomato by overexpression of multi-domain proteinase inhibitor CanPI7 gene against H. armigera larvae.

Isolation and characterization of 9-lipoxygenase and epoxide hydrolase 2 genes: insight into lactone biosynthesis in mango fruit (Mangifera indica L.) - Deshpande, Ashish B.; Chidley, Hemangi G.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2017)
Uniqueness and diversity of mango flavour across various cultivars are well known. Among various flavour metabolites lactones form an important class of aroma volatiles in certain mango varieties due to their ripening specific appearance and lower odour detection threshold. In spite of their biological and biochemical importance, lactone biosynthetic pathway in plants remains elusive. Present study encompasses quantitative real-time analysis of 9-lipoxygenase (Mi9LOX), epoxide hydrolase 2 (MiEH2), peroxygenase, hydroperoxide lyase and acyl-CoA-oxidase genes during various developmental and ripening stages in fruit of Alphonso, Paid and Kent cultivars with high, low and no lactone content and explains their variable lactone content. Study also covers isolation, recombinant protein characterization and transient over-expression of Mi9LOX and MiEH2 genes in mango fruits. Recombinant Mi9LOX utilized linoleic and linolenic acids, while MiEH2 utilized aromatic and fatty acid epoxides as their respective substrates depicting their role in fatty acid metabolism. Significant increase in concentration of delta-valerolactone and gamma-decalactone upon Mi9LOX over-expression and that of delta-valerolactone, gamma-hexalactone and delta-hexalactone upon MiEH2 over-expression further suggested probable involvement of these genes in lactone biosynthesis in mango. (C) 2017 Elsevier Ltd. All rights reserved.

Integrated transcriptomic and proteomic analyses suggest the participation of endogenous protease inhibitors in the regulation of protease gene expression in helicoverpa armigera - Lomate, Purushottam R.; Dewangan, Veena; Mahajan, Neha S.; Kumar, Yashwant; Kulkarni, Abhijeet; Wang, Li; Saxena, Smita; Gupta, Vidya S.; Giri, Ashok P. (Molecular & Cellular Proteomics, 2018)
Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant Capsicum annuum protease inhibitor-7 (CanPI-7) arrests growth and development of Helicoverpa armigera (Lepidoptera: Noctuidae). Using de novo RNA sequencing and proteomic analysis, we examined the response of H. armigera larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supporting a dynamic transition in H. armigera protease expression on CanPI-7 feeding with general down-regulation of protease genes at early time points (0.5 to 6 h) and significant up-regulation of specific trypsin, chymotrypsin and aminopeptidase genes at later time points (12 to 48 h). Further, coexpression of H. armigera endogenous PIs with several digestive protease genes were apparent. In addition to the differential expression of endogenous H. armigera PIs, we also observed a distinct novel isoform of endogenous PI in CanPI-7 fed H. armigera larvae. Based on present and earlier studies, we propose potential mechanism of protease regulation in H. armigera and subsequent adaptation strategy to cope with anti-nutritional components of plants.

Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.